ANALISIS PENGARUH ASUPAN MAKANAN LOKAL TERHADAP PENINGKATAN PRODUKTIVITAS KERJA PADA STASIUN PENYORTIRAN BUAH KELAPA SAWIT - Zulbaidi Zulbaidi; Chairiyaton Chairiyaton (Jurnal Optimalisasi, 2015)
Food is the main source of energy for the human body to perform its activities. Food eaten is transformed into calories. Caloric intake for labor is aimed to maintain and improve the health and seeking optimum working power, for it needs to be in accordance with the workload. The purpose of this research is to determine workload based on the classification workload (% CVL) on workers and determine the number of calories in food intake worker. Results of this study are expected to determine the workload so as to measure employee productivity can next evaluation to improve the productivity of the company's work.Keywords: Calorie, workload, productivity, CVL.